Association of Postoperative Neutrophil Lymphocyte Ratio (NLR) and Monocyte Lymphocyte Ratio (MLR) with the Presence of Osteoporosis in Japanese Patients after Hip Fracture Surgery: A Retrospective Cohort Study - Hirofumi Bekki; Takeshi Arizono; Daiki Hama; Akihiko Inokuchi; Takahiro Hamada; Ryuta Imamura (Journal of Osteoporosis)
Background. The diagnosis of osteoporosis is based on bone mineral density measurements expressed as a percentage of the young adult mean (YAM) in Japan. Osteoporosis is defined as YAM <70%, and intervention is recommended at this cutoff. Because osteoporosis has a strong association with systemic metabolic disorders, we postulated that patients with YAM <70% had higher inflammatory biomarker concentrations owing to the higher systemic stress compared with YAM >70%. Method. We retrospectively reviewed 94 patients with low-trauma hip fractures. Blood examinations were performed on postoperative day (POD) 1 and POD 7. We used neutrophil lymphocyte ratio (NLR) and monocyte lymphocyte ratio (MLR) to evaluate postoperative recovery. After dividing the 94 patients into two groups according to a YAM cutoff of 70%, we compared the differences in NLR and MLR. Results. On POD 1, patients with YAM >70% had a median NLR of 5.7 and a median MLR of 0.66, which were significantly lower than for patients with YAM <70% (8.8 and 0.9, respectively). Similarly, on POD 7, patients with YAM >70% had a median NLR of 2.0 and a median MLR of 0.31, which were significantly lower than for patients with YAM <70% (3.5 and 0.43, respectively). Conclusion. A YAM cutoff of 70% is an appropriate intervention threshold regarding postoperative recovery after hip fracture surgery. Mini-Abstract. Patients with YAM >70% showed lower NLR and MLR on POD 1 and POD 7. A YAM cuffoff of 70% is an appropriate intervention threshold regarding postoperative recovery after hip fracture surgery.